Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1902/jop.2012.120165
|View full text |Cite
|
Sign up to set email alerts
|

Cyanoacrylate Versus Laser in the Treatment of Dentin Hypersensitivity: A Controlled, Randomized, Double‐Masked and Non‐Inferiority Clinical Trial

Abstract: It was concluded that cyanoacrylate is as effective as low-intensity laser in reducing DH. In addition, it is a more accessible and low-cost procedure and can be safely used in the treatment of DH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 28 publications
(67 reference statements)
1
49
0
3
Order By: Relevance
“…After analyzing the full text from 24 clinical trials, 17 were excluded (Table1) because they did not fulfill all the selection criteria [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Our final review included 7 articles [9][10][11][12]30,31,32 . Demographic details and General characteristics of included studies were described in table 2,3 & 4.…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…After analyzing the full text from 24 clinical trials, 17 were excluded (Table1) because they did not fulfill all the selection criteria [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Our final review included 7 articles [9][10][11][12]30,31,32 . Demographic details and General characteristics of included studies were described in table 2,3 & 4.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Among these five studies three studies 9,10,31 reported the efficacy of combined effect of lasers and topical desensitising agents, of which two studies 9.10 reported that the combination of laser and topical de sensitizing agent showed greater efficacy whereas one study 31 reported that combination of laser and topical de sensitizing agent did not show greater efficacy compared to laser used alone. Remaining two studies 11,12 reported that both lasers and topical desensitising agents were equally effective in reducing dentinal hypersensitivity.…”
Section: Gaalas Laser Versus Control Groupmentioning
confidence: 99%
“…Há muitos relatos com relação à utilização dos lasers de baixa intensidade para o tratamento da hipersensibilidade dentinária. A melhora na sintomatologia dolorosa a estímulos térmicos e tácteis, bem como efeitos analgésicos imediatos e que se prolongam por certo período de tempo foram relatados 10,[15][16][17] . Apesar da ação do laser de baixa intensidade não estar totalmente esclarecido, acredita-se que o efeito imediato do laser de baixa intensidade na hipersensibilidade dentinária baseia-se, principalmente, nas alterações induzidas nas redes de transmissão nervosa dentro da polpa dentária ao invés de alterações nos túbulos dentinários expostos, como é observado em outras modalidades de tratamento.…”
Section: Laser De Baixa Intensidadeunclassified
“…A aplicação do laser de baixa intensidade deverá ser realizada em quatro pontos diferentes: um ponto no ápice da raiz e três pontos na região cervical do dente que apresenta a dentina exposta (geralmente nas faces mésio-vestibular, vestibular e disto vestibular), com dosagem em torno de 3,5 a 4,0J/cm 2,17,19,21 . O tratamento da hipersensibilidade dentinária cervical com lasers de baixa intensidade é um método biocompatível, não-invasivo e eficiente 16,22 .Para esta modalidade de tratamento, são utilizados, principalmente, os lasers diodo, cujo meio ativo é composto por HeNe (Hélio-Neônio) e GaAlAs (Arseneto de Gálio-Alumínio), que possuem comprimento de onda, respectivamente, em torno de 633 e 810 nm e são muito utilizados para a bioestimulação pós-operatória de cirurgias orais, graças à sua afinidade com os componentes dos tecidos moles 15 . Apesar do mecanismo de ação do laser de baixa intensidade ainda não se apresentar totalmente conhecido, acredita-se que a irradiação da dentina exposta estimule as células nervosas do tecido pulpar, interferindo na polaridade das membranas celulares pelo aumento da amplitude do potencial de ação, o que leva ao bloqueio da transmissão do estímulo nervoso 19 .…”
Section: Laser De Baixa Intensidadeunclassified
See 1 more Smart Citation